Anchored on looks an exploratory study on beauty standards set to women broadcast journalists in the top three television networks in the Philippines - Esteban, Patricia Kaye Bernanrdo
The concept of beauty has varied through society's different perspectives. However, throughout the past years, its implications were geared specifically to women. For this study, the researchers wanted to shed light on the standards of beauty imposed on women broadcast journalists in GMA, ABS-CBN, and CNN Philippines respectively. The study was viewed from the lens of Naila Kabeer's Social Relations Approach to ascertion where preexisting notions of gender inequality came from. The researchers conducted in-depth and structured interviews with the broadcast journalists themselves as well as their stylists and make-up artists to aid in the analysis. In order to synthesize the findings, the researchers found it essential to interview an expert on women studies expert to further understand why women broadcast journalists follow these so-called beauty standards. Using these data, the researchers concluded that make-up, wardrobe, hairstyle, and overall physical appearance of a woman broadcast journalist were not necessarily perceived as 'beauty standards. But rather, these are perceived as something connected to their job. However, women broadcast journalists continuously face challenges, stereotypes, and discrimination in society.